2013
DOI: 10.22136/est00201353
|View full text |Cite
|
Sign up to set email alerts
|

Mujeres y mercado de trabajo del turismo alternativo en Veracruz

Abstract: Resultado de su compromiso con una sustentabilidad social, el turismo alternativo es considerado una actividad para potenciar cambios en la tradicional división del trabajo. En esta investigación cualitativa se revisa la participación de las mujeres en el turismo alternativo del estado de Veracruz y se visibilizan segregaciones ocupacionales y simultaneidad en la realización de trabajo productivo-reproductivo y de cuidados. El enfoque de género se muestra como una herramienta potencial para observar el trabajo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
3
0
7
Order By: Relevance
“…We also found that the hospitality industry reproduces the gender structure by segregating women into basic cleaning positions that reproduce domestic labor. This has been previously documented by several authors who have found that this is common in the job market and that it is particularly common in the hospitality industry [ 32 , 33 , 34 , 35 , 36 , 37 ]. These findings moved us to question the motives behind employers assigning lower qualification positions mostly to women, regardless of their education level.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…We also found that the hospitality industry reproduces the gender structure by segregating women into basic cleaning positions that reproduce domestic labor. This has been previously documented by several authors who have found that this is common in the job market and that it is particularly common in the hospitality industry [ 32 , 33 , 34 , 35 , 36 , 37 ]. These findings moved us to question the motives behind employers assigning lower qualification positions mostly to women, regardless of their education level.…”
Section: Resultsmentioning
confidence: 58%
“…Contrary to this, by working, women feel like they are not fulfilling their traditional role of being dedicated only to caregiving and caring for the household. As has been detailed by Díaz-Carrión (2013), Lara-Aldava and Vizcarra-Bordi (2008), Martínez (2003), Mendoza and Chapulín (2015), Soares, Castorena and Ruiz (2005) and Vargas (2010) [ 32 , 33 , 34 , 35 , 36 , 37 ], the tourism sector perpetuates the patriarchal structure of power and gender inequality in México. In the organizational functionality of the hospitality industry, labor segregation by gender prevails in the form of differentiating activities and positions mimicking social functions and roles [ 38 ].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Por ello se buscó establecer una relación de confianza con quienes son dueños de los ejidos y comunidades cercanas, y así captar su realidad, ya que el solo uso de métodos cuantitativos resulta corto para entender la dinámica de organización, formas de vida y relatos personales que guardan pensamientos, conductas y emociones reflejadas en la toma de decisiones de los actores (Díaz-Carrión, 2014).…”
Section: Marco Metodológicounclassified
“…Hasta ahora este tipo de metodología se ha utilizado en trabajos relacionados con temas del turismo comunitario, del empoderamiento de género en comunidades, y de los impactos del turismo (Cambero, 2011;Díaz-Carrión, 2014;Sánchez, 2009); pero muy poco sobre el tema del turismo arqueológico de forma específica para el estado de Quintana Roo, ya que el término de turismo arqueológico no es utilizado por la Secretaría de Turismo, y ésta lo ve en conjunto como parte del turismo cultural del país. Más aún, al relacionarse el turismo arqueológico con la economía local, como se desarrolla en líneas abajo.…”
Section: Marco Metodológicounclassified